Increasing Methane Emissions and Widespread Cold‐Season Release From High‐Arctic Regions Detected Through Atmospheric Measurements - Ward, Rebecca H.; Sweeney, Colm; Miller, John B.; Goeckede, Mathias; Laurila, Tuomas; Hatakka, Juha; Ivakov, Viktor; Sasakawa, Motoki; Machida, Toshinobu; Morimoto, Shinji; Goto, Daisuke; Ganesan, Anita L. (John Wiley & Sons, 2025)
Rising Arctic temperatures pose a threat to the large carbon stores trapped in Arctic permafrost. To assess methane emissions in high-Arctic regions, we analyzed atmospheric data from Alaska and Siberia using two methods: (a) a wind sector approach to calculate emission changes based on concentration enhancements using wind direction, and (b) an inversion method utilizing a high-resolution atmospheric transport model. Incorporating data after 2015, we observed a significant rise in methane emissions (0.018 ± 0.005 Tg yr−2 from 2000 to 2021) from Alaska's North Slope, indicating a shift from previous analyses. We find 34%–50% of yearly emissions occurred in the late season (September–December) consistently across multiple years and regions, which is historically underestimated in models and inventories. Our findings reveal significant changes occurring in the Arctic, highlighting the crucial role of long-term atmospheric measurements in monitoring the region, especially during the cold season.